Pregnancy Outcomes Following Bariatric Surgery - Aloufi, Widad; Othman, Basil M.; Othman, Mohammad (British Journal of Healthcare and Medical Research, 2022)
Obesity in Saudi Arabia is three times the global average. Bariatric surgery as a fast solution to obesity problems associated with higher rate of Diabetes mellitus remission. In gestational diabetes mellitus, bariatric surgery in small scale studies showed promising outcomes for both the mother and the infant. This study investigated gestational diabetes mellitus and perinatal outcomes in women with history of bariatric surgery compared to matched women without such a history. In this retrospective multicenter cohort study in Al-Baha area, 2412 women were included. This study concluded that bariatric surgery may be associated with reduced risks of gestational diabetes, macrosomia, operative deliveries, congenital malformation and neonatal mortality. Also, this study showed the need for nationwide studies on such important issue.